Sustaining pulses production through effective weed management options - Ghosh, Sonaka; Das, T K; Upadhyaya, Ashutosh (Indian Farming, 2023)
India is the world's leading producer of pulses. Pulses not only provide nutritionally rich food and feed, but they also improve soil health and crop productivity. Weeds are the most significant biological constraint in pulse production. According to research, weeds alone reduce pulse crop yields by 20 to 40%. Efficient weed management practices are critical in increasing pulse yield. Differentweed management strategies such as broad-spectrum herbicides, bio-herbicides, biotechnological approaches along with improved resource conservation technologies must be used along with good agronomic practices to ensure efficient weed control. Integrated weed management has the potential to increase productivity and profitability by making better use of resources and suppressing weeds. For pulse productivity to be sustained, an economically viable weed management strategy must be identified.